STRATEGI PENANGANAN KAWASAN PERMUKIMAN KUMUH OLEH DINAS PERUMAHAN, KAWASAN PERMUKIMAN DAN PERTANAHAN KOTA BEKASI (Studi Kasus pada Kelurahan Medan Satria) - Nabilah Az Zahra; Eka Yulyana (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2025)
The emergence of slum settlements in Bekasi City is caused by the rapid development of the city and high urbanization, which causes population density to Housing, Settlement Areas and Land, is committed to overcoming this problem and improving the conditions of these settlements. The aim of this research is to determine the strategy for handling slum areas by the Bekasi City Housing, Settlement and Land Services Department. This research adopts the Strategy Theory proposed by Geoff Mulgan (2009) which includes goals, environment, direction, action and learning. The method used is a qualitative research method with data collection techniques using interviews, direct observation, documentation and physical devices. The research results show that the Department of Housing, Settlement Areas and Land is committed to creating slum-free areas by 2030 through various activities such as building environmental roads, repairing canals, providing clean water facilities, building septic tanks, and providing rutilahu assistance. This research also shows that the Department of Housing, Settlement Areas and Land has succeeded in taking into account external and internal factors in handling slum settlements, including challenges such as limited resources and coordination between related parties. These obstacles were successfully overcome through synergy with various institutions involved in the program. Keywords: Strategy, Management of Slum Settlements, Housing Department, Settlement Areas and Land